Silver Linings at the Dawn of a “Golden Age” - Britton, Kate; Crowley, Brooke E.; Bataille, Clément P.; Miller, Joshua H.; Wooller, Matthew J. (Frontiers in Ecology and Evolution, 2021)
Nearly four decades after the first applications of strontium isotope analyses in archaeology and palaeoecology research, it could be said that we are entering a ‘Golden Age’. Here, we reflect on major past developments and current strengths in strontium isotope research, as well as speculate on future directions. We review (1) the currently limited number of (but much needed) controlled feeding experiments, (2) recent advances in isoscape mapping and spatial assignment, and (3) the strength of multi-proxy approaches (including both the integration of strontium isotopes with other isotope systems and complementary techniques such as ancient DNA analyses). We also explore the integration of strontium isotope research with other types of palaeoecological or archaeological data, as well as with evidence and interpretative frameworks from other fields (such as conservation ecology, conservation palaeobiology or history). This blending is critical as we seek to advance the field beyond simply distinguishing local or relatively sedentary individuals from those that were non-local or highly mobile. We finish with a call for future research centred on balancing methodological developments and novel applications with critical self-reflection, deeper theoretical considerations and cross-disciplinarity.